Dampak Broken-Home Terhadap Perolehan Akademik Peserta Didik: Sebuah Studi Kasus - Sinta, Pelagia; Yuline, Yuline; Halida, Halida (Jurnal Bimbingan dan Konseling Ar-Rahman, 2025)
This study aims to describe counseling teachers' characteristics, learning outcomes, impacts, and efforts in addressing the effects of broken homes on student learning outcomes at SMP Negeri 4 Pontianak. The research utilized a qualitative approach with a descriptive method. Data was collected through interviews, observations, and documentation, with the researcher as the primary instrument. The data analysis involved stages of data reduction, data presentation, and drawing/verifying conclusions. The results indicated that students from broken homes in the first case exhibited disruptive behavior in class, lacked focus during lessons, failed to complete assignments, frequently used harsh language, skipped classes, were often angry, and achieved low learning outcomes in mathematics, with daily assignment scores of 0 and 70, and test scores of 30 and 50, against the minimum passing grade of 75. In the second case, the students demonstrated a lack of concentration, failed to complete tasks, often isolated themselves, cried frequently, daydreamed, became easily angered, and also had low math scores, with daily assignment scores of 0 and 70, and test scores of 50 and 70, also below the passing grade of 75. The impact of broken homes on these students included decreased learning outcomes, diminished interest in learning, frequent episodes of anger, and a tendency to isolate themselves. Counseling teachers addressed these issues by providing individual counseling services.    ____________________________________________________________ Penelitian ini bertujuan untuk menguraikan karakteristik, hasil belajar, dampak, serta upaya yang dilakukan oleh guru BK dalam menangani dampak broken home terhadap hasil belajar siswa di SMP Negeri 4 Pontianak. Penelitian ini menggunakan pendekatan kualitatif metode deskriptif. Pengumpulan data dilakukan melalui wawancara, observasi, dan dokumentasi, dengan human instrument sebagai instrumen utama. Analisis data meliputi tahapan reduksi data, penyajian data, dan penarikan kesimpulan/verifikasi. Hasil penelitian menunjukkan bahwa siswa yang mengalami broken home pada subjek pertama karakteristiknya sering mengganggu teman sekelas, kurang fokus saat belajar, tidak menyelesaikan tugas, sering berbicara kasar, membolos, sering marah, dan memiliki hasil belajar yang rendah dalam mata pelajaran matematika dengan nilai tugas harian 0 dan 70, serta nilai ulangan harian 30 dan 50 dari KKM 75. Pada subjek kedua, karakteristiknya mencakup kurang konsentrasi saat belajar, tidak menyelesaikan tugas, sering menyendiri, sering menangis, melamun, sering marah, dan juga memperoleh hasil belajar yang rendah dalam mata pelajaran matematika dengan nilai tugas harian 0 dan 70, serta nilai ulangan harian 50 dan 70 dari KKM 75. Dampak broken home pada siswa meliputi penurunan hasil belajar, menurunnya minat belajar, sering marah, dan kecenderungan untuk menyendiri. Guru BK mengatasi masalah ini dengan memberikan layanan konseling individual.